PERUBAHAN KARAKTERISTIK MEKANIS ASPAL YANG DITAMBAHKAN SULFUR SEBAGAI BAHAN TAMBAH - Mashuri, Mashuri; Patunrangi, Jurair (MEKTEK, 2011)
The purpose of this study is to observe the effect of sulfur on changes in mechanical properties of bitumenas a binder material. Usability research is expected to be preliminary information in estimating theadvantages and disadvantages of asphalt concrete when using material added sulfur.This research has been done in the Laboratory of Transportation and Highway, Faculty of EngineeringTadulako University, Palu.The scenario study was conducted with the manufacture of bitumen specimens with variation of sulfurcontent of 0.0%, 2.0%, 4.0%, 6.0%, 8.0% and 10.0% by weight of bitumen samples. Value mechanicalproperties of bitumen binder under study include the value of penetration, softening point, specific gravity ofbitumen, bitumen Flashpoint and Ductility. Method of inferential statistics (t-student test) at 5% significancelevel used to determine the effect of adding sulfur to the bitumen on the mechanical properties.The results of this study found that the addition of sulfur into the bitumen on the variation of 0% to 10%affect the mechanical properties of bitumen such as penetration, softening point, penetration index (PI), thespecific gravity of asphalt, asphalt ductility and Flashpoint. The study also found that the sulfur contentranges from 6% to 10% in bitumen tends to produce bitumen penetration index (PI) is positive (PI> 0) whichmeans the asphalt is less temperature susceptible.